Historia y bibliografía de la crítica sobre el Poema de mío Cid (1750-1971) - Magnotta, Miguel (Book collections on Project MUSE., 1976)
This book presents a chronological study of the critical and scholastic work on the Cid. It starts at the beginning of the Eighteenth-century with the rediscovery and the publication of the poem, and ends in 1971, just before the publication of one of the revolutionary modern editions of the text. The most impressive trait of this study is its exhaustiveness. It masterfully organizes a vast field of information in a comprehensive and accessible way. This volume is a very useful tool for any student of the Cid: from the novice to the most expert investigator.